Assessing the effectiveness of FDA regulation of energy drinks - Eno Buruwaa Boateng-Kagyah (KNUST, 2026)
A Thesis Submitted To The Department Of Food Science AND TECHNOLOGY, KWAME NKRUMAH UNIVERSITY OF SCIENCE AND TECHNOLOGY IN PARTIAL FULFILMENT OF THE REQUIREMENTS FOR THE DEGREE OF MASTER OF SCIENCE IN FOOD QUALITY MANAGEMENT